1998
DOI: 10.1002/(sici)1097-4695(19981105)37:2<265::aid-neu6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death of identified peptidergic neurons involved in ecdysis behavior in the moth,Manduca sexta

Abstract: The eclosion of the adult Manduca sexta moth is followed by a wave of cell death that eliminates up to 50% of the neurons of the central nervous system within the first few days of imaginal life. While the identity of some of the dying motoneurons has been established, that of most doomed neurons is unknown. Here, we show that the dying cells include peptidergic neurons involved in the control of ecdysis behavior. These cells belong to a small population of 50 neurons that express crustacean cardioactive pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…Maximal levels were observed just before adult emergence, consistent with the known role of bursicon in posteclosion tanning and sclerotization of the cuticle, wing inflation, and epidermal cell death (22). Earlier studies in moth (Manduca sexta) (24), locust (Schistocerca gregaria) (25), and Drosophila (26) demonstrated that most CCAP-expressing neurons undergo apoptosis after adult ecdysis, consistent with our findings of low transcript levels for pburs and burs in mature adult D. melanogaster. This low level of pburs and burs expression was accompanied by a reduction in the levels of DLGR2 message.…”
Section: Discussionsupporting
confidence: 91%
“…Maximal levels were observed just before adult emergence, consistent with the known role of bursicon in posteclosion tanning and sclerotization of the cuticle, wing inflation, and epidermal cell death (22). Earlier studies in moth (Manduca sexta) (24), locust (Schistocerca gregaria) (25), and Drosophila (26) demonstrated that most CCAP-expressing neurons undergo apoptosis after adult ecdysis, consistent with our findings of low transcript levels for pburs and burs in mature adult D. melanogaster. This low level of pburs and burs expression was accompanied by a reduction in the levels of DLGR2 message.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown that in newly eclosed mosquitoes, CCAP is highly expressed in neurons 27 and IN704 of the ventral nerve cord, but that these neurons undergo apoptosis by 12h post-eclosion (Honegger et al, 2011). This is similar to what has been reported for Manduca sexta immatures (Ewer et al, 1998;Davis et al, 2001). In the present study we show that in newly eclosed mosquitoes, neurons 27 extend numerous peripheral projections that span the pleuron and innervate the alary and cardiac muscles, as is also seen in M. sexta and Baculum extradendatum Ejaz and Lange, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…We have shown that the lateral pairs of 704 interneurons in the abdominal ganglia of larvae of M. sexta, and comparable neurons in B. mori, are MIP-immunoreactive, and this immunoreactivity is colocalized with that of CCAP. Ewer et al (1998) have demonstrated cell death of the 704 interneurons in fully mature M. sexta adults, and, as expected, we have found that in adults, these cells are not labeled by MIP-immunostaining.…”
Section: Role For Myoinhibitory Peptide In Insect Ecdysissupporting
confidence: 90%